Crystal structure of bis(μ2-azido-κ2N:N)-tetrakis(azido-κ1N)-tetrakis(1,10-phenanthroline-κ2N,N′)dibismuth(III), C48H32N26Bi2 - Zhong Zhi-Guo; Li Jing; Feng Yu-Quan (Zeitschrift für Kristallographie - New Crystal Structures)
C48H32N26Bi2, triclinic, P1‾$\overline{1}$ (no. 2), a = 9.781(5) Å, b = 11.667(6) Å, c = 11.973(7) Å, α = 83.816(10)°, β = 74.471(10)°, γ = 66.120(8)°, V = 1203.7 (11) Å3, Z = 1, Rgt(F) = 0.0435, wRref(F2) = 0.1035, T = 293 K.